Custom prosthetic replacement for distal radial tumours - Natarajan, Mayil Vahanan (Springer-Verlag, 2009)
We analysed the results of 24 cases of aggressive benign and malignant tumours of the distal radius treated by resection and prosthetic replacement between 1995 and 2006. Patient ages ranged from 18 to 74 years, averaging 33 years; 18 were males. Recurrent giant cell tumour was the most common tumour. The prosthesis used was a bipolar hinge custom mega prosthesis manufactured locally. Average follow-up was 78 months. The average Musculoskeletal Tumor Society (MSTS) functional score achieved was 75%. The ten-year prosthesis survival was rate 87.5%. Infection was the most common complication.